Visualizing urban sprawl to raise local awareness - Schaffert, Markus; Sahinkaya, Cemre; Wolff, Christian (Frontiers in Environmental Science, 2025)
Urban sprawl poses a significant challenge in the context of climate change. In Germany, while the tools for reducing land consumption are known, they are seldom employed due to a lack of local awareness. Building local support for land preservation is therefore a major challenge, impacting both public administrations responsible for designating new development areas and the general public. This paper proposes an approach to visualize the long-term development of urban sprawl at the local level, using historical geospatial data, including aerial imagery and maps predating satellite remote sensing. The aim is to create clear and easily understandable visualizations that demonstrate the dynamic expansion of built-up areas in municipalities over time. To this end, the paper identifies relevant data sources, processing steps, and presentation formats that can be applied in various contexts. The feasibility of this approach is illustrated by using three rural municipalities, showing how the visualizations can be concretely applied. The resulting visual representations are intended to be used in transformation workshops to stimulate discussion and raise awareness. Particular attention is given to the specific concerns of rural communities, with the goal of fostering greater citizen involvement and encouraging action to address urban sprawl.